2011
DOI: 10.1590/s0103-507x2011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Complicações e tempo de internação na revascularização miocárdica em hospitais públicos no Rio de Janeiro

Abstract: Complicações e tempo de internação na revascularização miocárdica em hospitais públicos no Rio de Janeiro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(33 reference statements)
0
3
0
3
Order By: Relevance
“…[11][12] Another study conducted in 2011 showed that the complications found post-CABG, were: hyperglycemia, blood transfusion, low cardiac arrhythmia, intra-aortic balloon, ventilatory prosthesis > 24 hours. 13 In a study by Soares and his collaborators, published in 2011, pointed out complications according to the organ or the affected area. These complications were distributed in: 11 pulmonary complications which have been found to tracheal intubation or mechanical ventilation for more than 48 hours after surgery, atelectasis, bronchoconstriction, hypoxemia, acute respiratory distress syndrome (ARDS), acute respiratory failure (PACA), pleural effusion, ventilator-associated pneumonia (VAP), acute lung edema, pneumothorax.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12] Another study conducted in 2011 showed that the complications found post-CABG, were: hyperglycemia, blood transfusion, low cardiac arrhythmia, intra-aortic balloon, ventilatory prosthesis > 24 hours. 13 In a study by Soares and his collaborators, published in 2011, pointed out complications according to the organ or the affected area. These complications were distributed in: 11 pulmonary complications which have been found to tracheal intubation or mechanical ventilation for more than 48 hours after surgery, atelectasis, bronchoconstriction, hypoxemia, acute respiratory distress syndrome (ARDS), acute respiratory failure (PACA), pleural effusion, ventilator-associated pneumonia (VAP), acute lung edema, pneumothorax.…”
Section: Resultsmentioning
confidence: 99%
“…Estudos apontam algumas complicações pulmonares no pós operatório de RM, dentre eles encontra-se o derrame pleural, atelectasia; pneumotórax, embolia pulmonar, insuficiência respiratória aguda; broncopneumonia, redução de volumes e capacidades pulmonares, alterações nas trocas de gasosa com consequente hipoxemia e diminuição da capacidade de difusão (9)(10) . Outro estudo realizado em 2011 apontou que as complicações encontradas pós-RM, foram: Hiperglicemia, hemotransfusão, baixo débito, arritmia, balão intra-aórtico, prótese ventilatória > 24 horas (11) .…”
Section: Resultsunclassified
“…Renal Aguda (IRA) (19) . Na IRA ocorre uma deterioração repentina da função renal, com perda da capacidade dos rins em realizar a excreção (20) .…”
Section: Discussionunclassified